The Role of The Security Department In Regulating The Discipline of Members of Student Organizations in Darussalam Gontor Modern Islamic Institution - Aldo Redho Syam; Muhammad Mukhlas (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Discipline is needed by humans for manage their lives and become useful for themselves and others. Discipline is also needed for an organizational success . the lives all members in student organization (OPPM), it is can't be separated from discipline. The Security Section as part of disciplinary enforcement emphasizes awareness, preventive measures and eliminates physical punishment to OPPM members. That matter to grow up awareness in OPPM members for application of discipline without a sense of compulsion. This research was conducted to determine the role of the Security section in carrying out tasks This research is a field research with descriptive qualitative type of analysis, to find data is related to this research, researcher use 3 data collection methods,: (1) documentation method, (2) observation method and (3) interview , while data analysis uses Spradley's qualitative data analysis, namely (1) domain analysis, (2) taxonomic analysis and (3) componential analysis. The results analysis data it was found that; (1) Discipline carried out by OPPM members is a good discipline, because they are obedient the Security section. (2) The role of the OPPM Security Section in regulating the discipline of OPPM members consists of: (a) As a provider of ideas (Innovator), (b) As a disciplinariy (Motivator), (c) As an accelerator in the growth of discipline awareness for OPPM members (Leader), (d) As an administrator who regulates the discipline (Manager).